Reactualizing Indonesia's Legal System: A Comprehensive Critique and Proposals for Reform - Vimelia, Willen; Aglia, Arla; Prabowo, Agung (International Journal of Humanities, Law, and Politics, 2024)
This text provides a comprehensive critique of the legal system and law enforcement in Indonesia, addressing challenges and proposing solutions. It discusses issues such as formalism, case backlog, and the need for innovation in judicial decision-making. The analysis emphasizes the importance of reactualizing the legal system, integrating local laws into the national framework, and implementing institutional reforms for law enforcement agencies. Additionally, the text advocates for empowering society through increased access to government functioning and legal awareness. The role of bureaucracy in development and challenges posed by political and constitutional phenomena are explored. The article outlines four key problems requiring attention: legal system reactualization, institutional restructuring, community empowerment, and bureaucratic empowerment. Ultimately, the analysis calls for a paradigm shift in legal philosophy and proposes improvements across various facets of Indonesia's legal system and law enforcement.